The Infocockpit: Providing Location and Place to Aid Human Memory - Tan, Desney; Stefanucci, Jeanine K.; Proffitt, Dennis R.; Pausch, Randy (Workshop on Perceptive User Interfaces 2001, 2001)
Our work focuses on building and evaluating computer system interfaces that make information memorable. Psychology research tells us people remember spatially distributed information based on its location relative to their body, as well as the environment in which the information was learned. We apply these principles in the implementation of a multimodal prototype system, the Infocockpit (for “Information Cockpit”). The Infocockpit not only uses multiple monitors surrounding the user to engage human memory for location, but also provides ambient visual and auditory displays to engage human memory for place. We report a user study demonstrating a 56% increase in memory for information presented with our Infocockpit system as compared to a standard desktop system.